Effect of longitudinal and cross feed on flatness and surface roughness in flat grinding - Zisov, Hristijan; Milkov, Dimitar; Cangulski, Atanas; Vasileska, Ema; Tuteski, Ognen; Kusigerski, Boban; CHaloska, Jasmina (University Library in Kragujevac, 2025)
This research focuses on analyzing the impact of longitudinal and cross feed on the grinding quality, with particular emphasis on the parameters of surface roughness and flatness of the machined surfaces. The main objective is to examine how different combinations of these parameters affect the surface roughness and flatness. The experimental study is conducted using a surface grinding machine, where roughness (Ra) and flatness are measured under various longitudinal and cross feed settings. A full-factorial experimental design is implemented to systematically analyze the interaction between these factors. Statistical methods, including regression analysis, are used to determine the significance of the variables and their effect on surface characteristics. The results indicate that both longitudinal and cross feed affect the roughness and flatness of the machined surfaces. These findings highlight the need to optimize process parameters to balance surface roughness and flatness for improved machining performance. The insights gained from this research provide valuable guidelines for optimizing grinding operations in industrial applications, ultimately enhancing efficiency and product quality.